A Comparative analysis of classic-Marxism and Neo-Marxism in the International Political Economy system - Muhammad Al Amin; MD Atikur Rahman Mir (HISTORICAL: Journal of History and Social Sciences, 2023)
This article focuses on Classic Marxism and Neo-Marxism. Classic Marxism originated in the early socialist era, inside the socialist labour movement, and specifically among its organizations and political parties. And Neo-Marxism Updates Marxist principles to account for the state of the world economy today. It rose to prominence in the 1960s and 1970s as technologists demonstrated that capitalism's policies stifled growth and widened the wealth gap between the North and South. In this paper, the authors tried to do a comparative analysis of classic Marxism and Neo-Marxism in the International Political Economy (IPE) system.